Concept and Division of Law in Islam: A Study of Taklifi Law and Wadh'i Law - Muhammad Hudzaifah Al Zamzamy; Narendra Yudha Prawira Hadi; Gathan Pryatna Putra; Hanif Akmal Zahardi; Muhammad Ariq Ulin Nuha; Muhammad Fachri Al Ikhsan; Taufiq Kurniawan (LP3M Pascasarjana STAI Ibnurusyd, 2026)
Sharia law (hukum syara’) refers to the rules established by Allah SWT to regulate the behavior of human beings who have met the requirements to receive and carry out legal responsibilities in Islam (mukallaf). These rules are derived from the Qur'an and Hadith and represent a central topic in the study of ushul fiqh, which aims to understand the principles and foundations of Islamic legal rulings in a systematic and structured manner. By understanding Sharia law, Muslims are able to guide their attitudes and actions in accordance with Islamic teachings in various aspects of life. Scholars in many academic works explain that Sharia law is generally divided into two main categories: taklifi law and wadh’i law. Taklifi law consists of rulings that contain direct demands addressed to the mukallaf, either in the form of commands to perform certain actions, prohibitions against performing them, or choices between performing or not performing an action. This category includes five primary rulings: obligatory, recommended, prohibited, disliked, and permissible, each indicating different levels of obligation in Islamic practice. Meanwhile, wadh’i law functions to determine when taklifi law becomes applicable through several elements, such as cause, condition, impediment, validity and invalidity, as well as strict rulings and legal concessions. This classification demonstrates that Islamic law is systematic and flexible, allowing it to regulate human behavior in a balanced way while fulfilling the objectives of Sharia, namely achieving benefit and preventing harm in human life.